2009
DOI: 10.1029/2009jb006344
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric effects and spurious signals in GPS analyses

Abstract: [1] Improvements in the analyses of Global Positioning System (GPS) observations yield resolvable millimeter to submillimeter differences in coordinate estimates, thus providing sufficient resolution to distinguish subtle differences in analysis methodologies. Here we investigate the effects on site coordinates of using different approaches to modeling atmospheric loading deformation (ATML) and handling of tropospheric delays. The rigorous approach of using the time-varying Vienna Mapping Function 1 yields sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
136
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(146 citation statements)
references
References 45 publications
7
136
0
3
Order By: Relevance
“…The conventional recommendation is to calculate the station displacement using the Ray and Ponte (2003) tidal model. However, crustal motion related to non-tidal atmospheric loading has been detected in station position time series from space geodetic techniques (van Dam et al, 1994;Mangiarotti et al, 2001;Tregoning and Van Dam, 2005). Several models of station displacements related to this effect are currently available.…”
Section: Impact Of Non-tidal Atmospheric Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional recommendation is to calculate the station displacement using the Ray and Ponte (2003) tidal model. However, crustal motion related to non-tidal atmospheric loading has been detected in station position time series from space geodetic techniques (van Dam et al, 1994;Mangiarotti et al, 2001;Tregoning and Van Dam, 2005). Several models of station displacements related to this effect are currently available.…”
Section: Impact Of Non-tidal Atmospheric Loadingmentioning
confidence: 99%
“…To evaluate their impact, two solutions, one with and one without a non-tidal atmospheric loading model, have been compared for the year 2013. In the solution with the model, the National Centers for Environmental Prediction (NCEP) model is used at the observation level during data reduction (Tregoning and Watson, 2009). Dach et al (2010) have already found that the repeatability of the station coordinates improves by 20 % when applying the non-tidal atmospheric loading correction directly on the data analysis and by 10 % when applying a postprocessing correction to the resulting weekly coordinates.…”
Section: Impact Of Non-tidal Atmospheric Loadingmentioning
confidence: 99%
“…3). Other studies (Amiri-Simkooei et al 2007;Ray et al 2008;Tregoning and Watson 2009) have shown that the observed ∼annual and ∼semiannual peaks in power spectra of GPS timeseries are really GPS draconitic annual (∼351.4 days) and semiannual (∼175.7 days) periods. A GPS draconitic year is the period for the GPS constellation to repeat its orientation relative to the Sun (Ray et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous sources of uncertainties affect GPS velocity estimations, especially in the vertical component: e.g., reference frame errors (Argus et al, 1999), seasonal signals (Blewitt and Lavallée, 2002), and atmospheric loading effects (Tregoning and Watson, 2009). These various sources of noise and non-tectonic signals can result in artificial trends over several years and systematic biases that may be correlated over large regions.…”
Section: Introductionmentioning
confidence: 99%